The Muslim-Croat Civil War in Central Bosnia : A Military History, 1992-1994 - Shrader, Charles R. (Book collections on Project MUSE., 2003)
"In this volume Charles R. Shrader offers the first full-scale military history of a crucial conflict in Bosnia between two former allies. When the Bosnian Serbs and their Serbian allies attacked Bosnia-Herzegovina in March, 1992, the Bosnian Croats and Muslims collaborated to defend themselves." "Drawing on testimony and exhibits from cases presented before the International Criminal Tribunal for the former Yugoslavia, Shrader describes the organization and tactical doctrine of the Croatian Defense Forces and the Muslim-led Army of Bosnia-Herzegovina. He analyzes the strengths and weaknesses of the two sides in such fields as communications, training, and logistics. He assesses not only the problems of command and control in the newly formed armies, but also the impact of criminal activity, the mujahedeen, and the intervention of peacekeeping forces." "Although Shrader's work is a detailed analysis by a neutral expert, not everyone will find his conclusions comfortable. But every serious student of the conflict in Bosnia will have to take his history into account. Enhanced by maps, useful appendices, and a glossary, this should become the standard work on military operations in Central Bosnia and a useful case study of internal warfare and ethnic conflict."--Jacket